Sinusoidal CO2 respiratory challenge for concurrent perfusion and cerebrovascular reactivity MRI - Vu, Chau; Xu, Botian; González-Zacarías, Clio; Shen, Jian; Baas, Koen P. A.; Choi, Soyoung; Nederveen, Aart J.; Wood, John C. (Frontiers in Physiology, 2023)
Deoxygenation-based dynamic susceptibility contrast (dDSC) has previously leveraged respiratory challenges to modulate blood oxygen content as an endogenous source of contrast alternative to gadolinium injection in perfusion-weighted MRI. This work proposed the use of sinusoidal modulation of end-tidal CO2 pressures (SineCO2) to induce susceptibility-weighted gradient-echo signal loss to measure brain perfusion. SineCO2 was performed in 10 healthy volunteers (age 37 ± 11, 60% female), and tracer kinetics models were applied in the frequency domain to calculate cerebral blood flow, cerebral blood volume, mean transit time, and temporal delay. These perfusion estimates were compared against three reference techniques, gadolinium-based DSC, arterial spin labeling, and phase contrast. Our results showed regional agreement between SineCO2 and the clinical comparators. SineCO2 was able to generate robust CVR maps in conjunction to baseline perfusion estimates. Sinusoidal CO2 respiratory paradigms can be used to simultaneously acquire both cerebral perfusion and cerebrovascular reactivity maps in one imaging sequence.